Waste-based panels with cement grout as an infill material for composite railway sleepers - Mamun Abdullah; Wahid Ferdous; Sourish Banerjee; Ali Mohammed; Allan Manalo (Results in Engineering)
The development of high performance and eco-friendly composite railway sleepers at a reasonable price is a great challenge for composite railway sleeper manufacturers. The study proposed a railway sleeper concept based on high-performance fibre composites and low-cost waste-based materials to overcome this challenge. In this concept, thin hollow composite tubes are filled with high volume waste-based panels, which are bonded together with cement grout. This study examined the effect of cement grout, grout thickness, panel types, and surface preparation of the panels on the bond behaviour between the panels and cement grout. It also investigated the bending behaviour of manufactured railway sleepers by evaluating the effects of filling hollow tubes, the orientation of the infill panels, and the types of infill materials. Results indicate that the proposed concept has a high potential for development of high performance and eco-friendly composite railway sleepers at a competitive price due to the incorporation of high volume of waste materials. The results of the study will serve as a guide to the manufacture and design of composite railway sleepers.